A class perspective on gender inequality: How welfare states shape the gender pay gap - Hadas Mandel; Michael Shalev (Luxembourg Income Study (LIS), 2006)
The gender division of paid labor is embedded within systems of class stratification. The gap between the average earnings of men and women derives from the tendency for women to occupy inferior class positions and thereby to disproportionately pay the price of class inequality. From a class perspective, welfare states have multiple impacts on the gender pay gap. They influence women's class locations and also shape inequality between and within classes. We theorize and test the effects of three dimensions of welfare regimes on three components of the gender gap. Using both income and occupation-based measures of class and microdata for 17 post-industrial societies, we reveal systematic regime-level variation. The results resolve previous puzzles by showing that multiple aspects of welfare regimes have different and often contradictory effects on the class/gender components of the wage gap. Women face distinct tradeoffs across welfare regimes, depending on their class positions.
Keywords: 330; Lohnstruktur; Soziale Schicht; OECD-Staaten; Geschlechterdiskriminierung